2006
DOI: 10.1007/s11130-006-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cultivar, Year Grown, and Cropping System on the Content of Tocopherols and Tocotrienols in Grains of Hulled and Hulless Barley

Abstract: In a three-year period (2000-2002) total tocols (tocopherols and tocotrienols), content of vitamin E and its isomers (alpha-, beta+gamma-, delta-tocopherols and tocotrienols) were assessed in grain of 13 barley genotypes. The highest content of tocols (60.3-67.6 mg kg(-1)) and content of vitamin E (Vitamin E equivalent-18.0-20.1 mg kg(-1)) were determined in the waxy varieties Wanubet, Wabet, and Washonubet. Standard varieties, i.e. of a malting type (Krona and Kompakt), had statistically significantly lower c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
56
0
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 14 publications
9
56
0
13
Order By: Relevance
“…The hulless barley genotypes included in this study showed rather high variability in a-tocopherol content (3.3-8.7 mg kg -1 ).These results were similar to those reported by Ehrenbergerova et al (2006) study in the Czech Republic, in which the average á-tocopherols content was 6.7 mg kg -1 . In Italy, for hulless varieties the a-tocopherol content was higher (8.4 to 10.1 g kg -1 ) and for covered varieties -8.4-8.6 g kg -1 (Cavarello et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The hulless barley genotypes included in this study showed rather high variability in a-tocopherol content (3.3-8.7 mg kg -1 ).These results were similar to those reported by Ehrenbergerova et al (2006) study in the Czech Republic, in which the average á-tocopherols content was 6.7 mg kg -1 . In Italy, for hulless varieties the a-tocopherol content was higher (8.4 to 10.1 g kg -1 ) and for covered varieties -8.4-8.6 g kg -1 (Cavarello et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…In Italy, for hulless varieties the a-tocopherol content was higher (8.4 to 10.1 g kg -1 ) and for covered varieties -8.4-8.6 g kg -1 (Cavarello et al, 2004). Genotype and growing conditions are known to significantly affect the content of a-tocopherol (Zilienski et al, 2001;Ehrenbergerova et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Key steps to overcome this problem include the exploration, preservation, and utilization of diversity within germplasm resources (Ma, 2002). A large number of researchers have studied hulless barley based on morphology (Badr et al, 2000;Meng and Zhao, 2006), biochemistry (Izydorczyk et al, 2000;Ehrenberová et al, 2006;Han et al, 2010), cytology (Singh et al, 1970;Søgaard and Wettstein-Knowles, 1987;Zhang, 2000), and molecular biology (Zeng et al, 2002;Feng et al, 2003;Zhang, 2004). However, the use of morphological traits remains the most basic method to analyze initial germplasm resources.…”
Section: Introductionmentioning
confidence: 99%
“…Je zajímavé, že právě v zrnu ječmene je zastoupeno všech osm izomerů vitamínu E, tj. α-, β+γ-, δ-tokoferoly a α-, β+γ-, δ-tokotrienoly, které chrání obilku před oxidací během skladování a klíčení [6,7,8,9,10], což je důležité pro výrobu sladu. Peterson [8] udává, že v klíčku obilky je obsažen izomer α-tokoferol a menší množství γ-, δ-tokoferolů a β-tokotrienolu.…”
unclassified
“…Ostatní izomery jsou zastoupeny v pluše a endospermu obilky, kde je v největším množství obsažen α-tokotrienol. Ehrenbergerová et al [7] zjistili signifikantně vyšší množství vitamínu E v obilkách bezpluchých waxy genotypech ječmene oproti odrůdám sladovnickým s pluchatými obilkami.…”
unclassified